2008
DOI: 10.3325/cmj.2008.5.608
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Vascular Endothelial Growth Factor and Nuclear Factor-κB in Renal Cell Tumors

Abstract: Aim To assess the relationship between protein and messenger RNA (mRNA) levels of vascular endothelial growth factor (VEGF) and subcellular localization of nuclear factor-kappa B (NF-κB), proliferation rate of tumor cells, and clinicopathological characteristics of renal cell tumors.Methods We analyzed 31 one renal cell tumors -22 clear cell renal cell carcinomas (CCRCC) and 9 other histologic types (non-CCRCC). VEGF expression and subcellular localization of p65 member of NF-κB and Ki67 were immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
(27 reference statements)
2
9
1
Order By: Relevance
“…Many renal cancer cells including the one used in this study are known to express increased levels of canonical NFκB subunits [48, 49, 53]. Additionally, nuclear localization of NFκB was observed in majority of the renal tumors, which was associated with rate of proliferation of tumor cells [51]. We show a correlation between increased miR-21 and phosphorylated active NFκB due to upregulated active IKKβ.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Many renal cancer cells including the one used in this study are known to express increased levels of canonical NFκB subunits [48, 49, 53]. Additionally, nuclear localization of NFκB was observed in majority of the renal tumors, which was associated with rate of proliferation of tumor cells [51]. We show a correlation between increased miR-21 and phosphorylated active NFκB due to upregulated active IKKβ.…”
Section: Discussionmentioning
confidence: 68%
“…Recently Sourbier et al reported significant increase in levels of p65 and phosphorylated p65 in a cohort of patients with renal cell carcinoma [49]. Using renal tumor tissue, two more studies also showed increased expression of NFκB subunits that was associated with increased growth factors and anti-apoptotic proteins [50, 51]. Furthermore, a more recent study demonstrated that 70% of renal tumors possess activated NFκB [52].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the ins allele played an important role in the susceptibility to ulcerative colitis, oral squamous cell carcinoma and psoriasis [30,33,34]. Accumulating evidence suggested that NF-ĸB was constitutively activated in RCC tumors [35,36,37]. Konda et al [38] reported that overexpression of NF-ĸB may be involved in the development of renal cysts and their subsequent transformation into tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of numerous genes related to various events such as cell proliferation, inflammation and inhibition of apoptosis, is under the influence of this transcription factor (7), its deregulation being associated with almost all types of cancer (11,12). Particularly, different authors have reported an NF-κB overexpression in RCC tumors and cell lines (12)(13)(14)(15), and in certain publications this overexpression has been correlated to tumor grade, invasion and metastasis, proposing the factor as a target for RCC treatment (2,3,14,16). In fact, apoptosis-induction and/or growth-repression of different RCC cell lines have been demonstrated by using a specific inhibitor of NF-κB activation (Bay- or by blocking tyrosine kinases involved in NF-κB activation signaling (17,18).…”
Section: Introductionmentioning
confidence: 99%